Efficacy of a Low-threshold, Culturally-Sensitive Group Psychoeducation Programme for Asylum Seekers (LoPe): Study protocol for a multicentre randomised controlled trial - Weise, Cornelia; Grupp, Freyja; Reese, Jens-Peter; Schade-Brittinger, Carmen; Ehring, Thomas; Morina, Nexhmedin; Stangier, Ulrich; Steil, Regina; Johow, Johannes; Mewes, Ricarda (BMJ Open, 2021)
Introduction Despite high levels of mental distress, accessing psychological treatment is difficult for asylum seekers in Western host countries due to a lack of knowledge about mental disorders, and the health system, as well as due to cultural and language barriers. This study aims to investigate whether brief culturally sensitive and transdiagnostic psychoeducation is effective in increasing mental health literacy. Methods and analysis The study is a parallel two-group randomised controlled trial with 1:1 individual allocation to either culturally sensitive, low-threshold psychoeducation (‘Tea Garden’ (TG)) or a waitlist (WL) control group. It takes place at four study sites in Germany. A total of 166 adult asylum seekers who report at least mild mental distress will be randomly assigned. The TG consists of two 90 min group sessions and provides information about mental distress, resources and mental health services in a culturally sensitive manner. The primary outcome is the percentage of participants in the TG, as compared with the WL, achieving an increase in knowledge concerning symptoms of mental disorders, individual resources and mental healthcare from preintervention to postintervention. The further trajectory will be assessed 2 and 6 months after the end of the intervention. Secondary outcomes include changes in mental distress, openness towards psychotherapy and resilience. Furthermore, healthcare utilisation and economics will be assessed at all assessment points. Ethics and dissemination The study has been approved by the Ethics Commission of the German Psychological Society (ref: WeiseCornelia2019-10-18VA). Results will be disseminated via presentations, publication in international journals and national outlets for clinicians. Furthermore, intervention materials will be available, and the existing network will be used to disseminate and implement the interventions into routine healthcare. Trial registration number DRKS00020564; Pre-results. Protocol version 2020-10-06, version number: VO2F.
Keywords: depression & mood disorders; mental health; adult psychiatry; anxiety disorders